Variação nos hábitos alimentares da mosca de estábulos Stomoxys calcitrans L - Gonçalves,Neuza Maria Ferraz de Mello (1998)
During the course of a study on the behaviour, of Stomoxys calcitrans a research on the feeding habits of this fly was carried out. A total of 27l4 flies were caught in three poultry ranches from Araucária, Paraná. The source of the flie's sucked blood has been established by precipitin test. . The results showed that although almost all the flies usually feed mammal blood, some of them gave positive precipitin test for birds blood. Although all flies were caught on poultry ranches, none had feed on chickens but 2,7% of the total had feed on ducks, 0.7% on geese and 0.37% on turkeys.